Tri-ponderal mass index as a screening tool for obesity prediction in children aged 6–9 years - Niu, Yang; Zhang, Yajie; Sheng, Jinye; Lu, Wenyi; Li, Ji; Mao, Xiaomeng; Cai, Wei; Tang, Qingya; Shen, Xiuhua; Feng, Yi (Frontiers in Endocrinology, 2023)
Objective: This study aimed to evaluate the efficiency of tri-ponderal mass index (TMI) in determining obesity in Chinese children aged 6-9 years, using the criteria of percentage of body fat (PBF) and body mass index z-scores (BMI-Z).The cross-sectional study included 5365 children, aged 6-9 years, who participated in the project survey "Group prevention and treatment of obesity among students and school health promotion in Shanghai" from September 2007 to September 2009. Height, weight, waist circumference, body mass index (BMI), TMI, waist-to-height ratio (WHtR), and PBF were recorded. Statistical analyses including Kolmogorov-Smirnov test, chi-square test, receiver operating characteristics curve, and kappa chi-square test were performed.Results: TMI for both sexes was relatively constant with increasing age, and statistically significant differences were not observed at some ages (P > 0.05 at 6, 7, 8, and 9 years).WHtR showed subtle changes, while BMI and PBF increased significantly with age in boys and girls (P < 0.01). Using BMI-Z criteria as the measure of general obesity, the results indicated that TMI cutoff values for 6-9 years were 14.60 kg/m 3 for boys and 14.84 kg/m 3 for girls (P < 0.001). Analysis of the agreement between TMI and BMI-Z showed that the kappa statistic was 0.826 in boys and 0.709 in girls (P < 0.001).Conclusions: TMI, as a constant tool, holds great potential as an alternative screening method for identifying children aged 6-9 years who may be at risk of obesity at an early stage.